The Effects of Reading to Learn Pedagogy on Students’ Skills in Writing Recount Texts - Rifla Zalifatun Nasika Shofa; Dwi Agustina (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the effects of Reading to Learn pedagogy on students’ skills in writing recount texts and identified challenges encountered during its implementation. The study was conducted because many English as a Foreign Language students experienced difficulties in organizing ideas, controlling grammar, and constructing coherent recount texts. A pre-experimental design with one-group pre-test and post-test was employed involving the eighth-grade students at SMP Negeri 7 Pekalongan, Central Java. Quantitative data were collected through writing tests administered before and after the implementation of Reading to Learn pedagogy, while observational data were used to identify challenges during the teaching and learning process. The quantitative data were analyzed using descriptive statistics, normality testing, and paired-sample t-test analysis. The findings revealed that the students’ mean score improved from 67.0345 in the pre-test to 84.8276 in the post-test. The paired-sample t-test showed a statistically significant difference between the pre-test and post-test results with a significance value lower than 0.05, indicating that Reading to Learn pedagogy effectively improved students’ recount writing skills. The observational findings further revealed several challenges, including limited instructional time, students’ difficulties in grammar and vocabulary control, and students’ dependence on teacher scaffolding during independent writing activities. Overall, the study concluded that Reading to Learn pedagogy effectively improved students’ recount writing skills through structured and scaffolded literacy instruction.